Exploring the effectiveness of podcasts in improving sexual health among young people: Findings from a qualitative study - Yixuan Zou; Albie Sharpe; Maddison Stratten; Daniel Demant (PLoS ONE, 2026)
Background Sexual health promotion among young people remains an urgent global priority. Despite robust public health systems, young people living in Australia continue to experience unmet needs in sexual health promotion due to cultural stigma, lack of relatable content, and insufficient inclusivity for marginalised populations. Podcasts are gaining attention as a flexible, relatable medium that may address these gaps, yet little research has explored their effectiveness in sexual health promotion from young people’s perspectives. This study aimed to explore how the On The Couch podcast supports young people’s sexual health. Methods This qualitative study conducted five focus groups with 18 participants aged 18–24 residing in Australia who had listened to the On The Couch sexual health podcast. Participants were recruited via university channels, social media, and podcast platforms, and reflected diverse cultural and educational backgrounds. Data collection involved semi-structured focus groups conducted both online and face-to-face. Transcripts were analysed using Braun and Clarke’s thematic analysis approach to identify themes and sub-themes. Ethical approval was granted by the Greater Western Human Research Ethics Committee (Reference: 2023/ETH02655) with ratification from the University of Technology Sydney Medical Research Ethics Committee. Results Three major themes emerged from the analysis: (1) Podcasts significantly improved knowledge and shifted attitudes toward sexual health through relatable storytelling and emotional resonance. However, translating awareness into sustained behavioural change remained challenging, largely due to cultural and structural barriers. (2) Young people valued podcasts for their conversational tone, accessibility, and convenience, but highlighted the need for multimodal enhancements such as visual aids and transcripts. (3) Participants offered specific recommendations for improving podcast design, advocating for increased youth co-creation, authentic narratives, interactive formats, and culturally sensitive content. Conclusions The study demonstrates that podcasts hold considerable promise for youth-focused sexual health promotion by providing relatable, emotionally engaging content. However, their effectiveness in changing behaviour is contingent upon addressing cultural barriers. Future podcasts should be developed with young people as co-creators, ensuring content aligns closely with their lived experiences, learning preferences, and social realities. This approach may enhance the role of podcasts as an effective medium in digital sexual health promotion.